Edukasi Pembuatan Asap Cair Dari Limbah Pertanian di Pokmas Dewi Sri Kabupaten Malang - Khalimatus Sa'diyah; Prayitno, Prayitno; Luchis Rubianto3; Profiyanti Hermien Suharti; Arief Rahmatulloh (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Liquid smoke, containing phenolic and acetic acid compounds with antimicrobial and antifungal properties, has potential as a biopesticide for pest and plant disease control. However, farmers have limited awareness and confidence in its effectiveness. To address this, technical training on liquid smoke application was conducted as part of the 2024 Community Service Program, aligned with the Tri Dharma of Higher Education. The program, implemented for Pokmas Dewi Sri in Jatiguwi Village, Sumberpucung District, Malang Regency, consisted of three stages: (1) initial discussions to identify issues, (2) education on converting agricultural waste into liquid smoke, and (3) evaluation. Training included an introduction to liquid smoke, its benefits, and hands-on production using pyrolysis of rice husks and straw at 350°C for two hours. Results showed that liquid smoke from these materials is effective as a biopesticide. Participants significantly improved their knowledge and skills in liquid smoke production and application. All ten Pokmas Dewi Sri members expressed high enthusiasm and provided positive feedback. This program enhances farmers’ capacity to utilize agricultural waste while reinforcing liquid smoke’s potential as an eco-friendly solution for sustainable pest control.